问题 解答题
计算.(能简算的要用简便方法计算)
(1)
4
9
÷6+
5
9
×
1
6
(2)12×(1-
2
3
÷
3
4
(3)(
21
26
×
13
7
+
1
2
)÷
2
5
(4)
8
9
×[
3
4
-(
7
16
-
1
4
)]
(5)10-(39÷
13
3
+
9
13
(6)2-(
1
4
+
1
7
)×
4
11
答案

(1)

4
9
÷6+
5
9
×
1
6

=

4
9
×
1
6
+
5
9
×
1
6

=(

4
9
+
5
9
)×
1
6

=

1
6

(2)12×(1-

2
3
÷
3
4
),

=12×(1-

8
9
),

=12×

1
9

=

4
3

(3)(

21
26
×
13
7
+
1
2
)÷
2
5

=(

3
2
+
1
2
)÷
2
5

=2÷

2
5

=5;

(4)

8
9
×[
3
4
-(
7
16
-
1
4
)],

=

8
9
×[
3
4
-
7
16
+
1
4
],

=

8
9
×[
3
4
+
1
4
-
7
16
],

=

8
9
×[1-
7
16
],

=

8
9
×
9
16

=

1
2

(5)10-(39÷

13
3
+
9
13
),

=10-(9+

9
13
),

=10-9

9
13

=

4
13

(6)2-(

1
4
+
1
7
)×
4
11

=2-

11
28
×
4
11

=2-

1
7

=

13
7

单项选择题
填空题